Soil organic carbon fraction mediated microbial community assembly along stand age and seasonal gradients in temperate poplar plantations - Xiangrong Liu; Changjun Ding; Lingyu Hou; Qiwu Sun; Weixi Zhang; Wenxu Zhu; Xiaohua Su; Zhongyi Pang; Rusheng Peng; Yanlin Zhang; Zhengsai Yuan (Plant and Soil, 2026)

The METTL14/YTHDF3 axis regulates EPSTI1-mediated osteogenic differentiation of human bone marrow mesenchymal stem cells - Changjun Zheng; Lingzhi Ding; Yan Xu; Chi Yuan; Bingjie Jiang; Tingting Chen; Yongjie Wang (Tissue and Cell, 2026)

The Effects of Poplar-Cyperus Esculentus Agroforestry System on Soil Nutrients and Microbial Communities in Northeast China - Wenxu Zhu; Weixi Zhang; Weiwei Gu; Xinyao Cong; Siqi Wu; Zhongyi Pang; Yanhui Peng; Jian Qiu; Zhuo sun; Changjun Ding (Journal of Soil Science and Plant Nutrition, 2026)

Optimizing thinning intensity for large-diameter poplar plantations: A UAV-LiDAR-based growth assessment - Tianle Li; Chenyan Lv; Qiang Guo; Dongdong Li; Bin Dong; Xuehai Tang; Junlong Liu; Tingting Miao; Changjun Ding; Youquan Jiao; Xiang Gao (Forest Ecology and Management, 2025)

Genetic mapping of quantitative trait loci conferring resistance to race 4 of Xanthomonas campestris pv. campestris in cabbage (Brassica oleracea var. capitata) - Qingguo Sun; Liang Yan; Changjun Ge; Jinlan Li; Junfen Dai; Hao Ding (Physiological and Molecular Plant Pathology, 2025)

RNA-Seq-based WGCNA reveals the physiological and molecular responses of poplar leaves to NaHCO3 stress - Song Jiaqi; Wang Jiechen; Qin Rui; Ji Guangxin; Cui Congcong; Sun Nan; Qi Siyue; Ding Changjun; Zhang Huihui (Trees, 2025)

Trees in cooler regions are more vulnerable to thermal stress: Evidence from temperate poplar plantations in Northern China during the 2022 heatwaves - Xin Kong; Shusen Zhang; Aoyu Wang; Yang Liu; Kai Wang; Xiaoning Zhao; Nan Di; Changjun Ding; Ximeng Li; Benye Xi (Agricultural and Forest Meteorology, 2024)

The beneficial and pathogenic flora, environmental drivers, and community assembly mechanism of perennial poplar plantation - Zhanbiao Li; Zhen Song; Rongye Qiao; Mingzhen Xu; Xinyan Wu; Yifan Chen; Pingdong Zhang; Changjun Ding; Yinglong Chen; Hui Guo (Plant and Soil, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Arbuscular mycorrhizal fungi communities vary between poplar species in the same habitat - Jiaying Liu; Wei Zhao; Yan Huo; Xinyao Cong; Yaguang Tian; Yuting Liu; Wenxu Zhu; Xiaohua Su; Weixi Zhang; Changjun Ding (Rhizosphere, 2024)

Physiology and transcriptomics reveal that hybridization improves the tolerance of poplar photosynthetic function to salt stress - Ding Changjun; Wang Yue; Zhang Weixi; Wang Jiechen; Song Jiaqi; Cui Congcong; Ji Guangxin; Ding Mi; Su Xiaohua; Zhang Huihui (Trees, 2024)

Matching root water uptake patterns to fine root and soil water distributions - Wei Zhu; Dehai Zhao; Nan Di; Doudou Li; Ou Zhou; Yiming Sun; Liming Jia; Changjun Ding; Benye Xi (Plant and Soil, 2024)

Effects of poplar agroforestry systems on soil nutrient and enzyme activity in the coastal region of eastern China - Cheng Xu; Zhuangzhuang Qian; Bo Wang; Tao Yang; Zeyang Lin; Di Tian; Changjun Ding; Luozhong Tang (Journal of Soils and Sediments, 2023)

Characteristics of Phyllosphere Microbial Communities Associated with Three Different Plants in the Semi-arid Areas of Northwest Liaoning - Keye Zhu; Wenxu Zhu; Weixi Zhang; Jiaying Liu; Changjun Ding (Journal of Soil Science and Plant Nutrition, 2023)

Community Characteristics of Soil Ectomycorrhizal Fungi under Different Forests in the Sandy Areas of Northeastern China - Jiaying Liu; Changjun Ding; Weixi Zhang; Yawei Wei; Yongbin Zhou; Wenxu Zhu (Journal of Soil Science and Plant Nutrition, 2023)

Characterization of ectomycorrhizal fungal communities associated with tree species on an iron tailings deposit undergoing restoration - Wenxu Zhu; Changjun Ding; Keye Zhu; Weixi Zhang; Dejun Liang; XiaoJiang Wang; Aiping Li; Xiaohua Su (Environmental Science and Pollution Research, 2022)
Vegetation restoration is an effective method to improve the ecological environment of mine tailings, which has a profound impact on the potential ecological functions of soil fungal communities; yet, little is known about its beneficial effect on soil ectomycorrhizal fungal community. In this study, the responses of soil characteristics and soil ectomycorrhizal fungal community diversity and structure to different revegetation, as well as the contribution of soil factors to soil ectomycorrhizal community were investigated in Liaoning Province, China. As we anticipated, the presence of vegetation significantly improved most soil properties we studied. What’s more, compared to Korean pine ( Pinus koraiensis Sieb. et Zucc.), Chinese poplar ( Populus simonii Carr), and black locust ( Robinia pseudoacacia L) could better improve soil total carbon, total nitrogen, total phosphorus, and available phosphorus. In addition, soil ectomycorrhizal fungal community diversity in black locust was greater than Korean pine and Populus simonii . Nonmetric multidimensional scaling analyses indicated that soil ectomycorrhizal community significantly differed depending on different revegetation types. Thus, these results indicated that black locust could be a suitable species for the revegetation of iron mine tailings. The study provided theoretical basis for ecological restoration of iron mine tailings using local plant species.

Production of an epigenetic mutant population of Populus nigra: DNA methylation and phenotype analyses - Shanchen Zhong; Yanan Gao; Junqian Lu; Changjun Ding; Xiaohua Su; Bingyu Zhang (Journal of Plant Biochemistry and Biotechnology, 2021)